Mucormycosis of the Middle Ear—A Report of a Rare Case - Madhu, Megha; Kamath P, Shrinath D.; Bhat, Vadisha; Srinivas, Teerthanath (Journal of Health and Allied Sciences NU, 2023)
Mucormycosis is an opportunistic fungal infection that often affects the nose and paranasal sinuses. The disease prevalence was very high in India during the coronavirus disease 2019 pandemic, thereby raising public awareness about this disease. The general practitioners were updated about the disease characteristics and the requirement for emergency management. Yet, in some instances, the treatment was inadequate due to delayed presentation and low affordability for treatment. The mucormycosis of the ear, on the other hand, is a rare occurrence that demands meticulous study for early diagnosis and management. Here, we discuss the case of a patient with mucormycosis of the middle ear.
Keywords: mucormycosis; middle ear; diabetic; facial palsy